The stranded whale - Yolen, Jane (Candlewick Press, 2015)
When Sally and her brother spot a beached whale on their way home from school in Maine, the town races to save the whale. Meanwhile, Sally sits close to the whale's eye and assures the stranded creature of its strength and beauty.